They don't get it, do they? : communication in the workplace--closing the gap between women and men - Reardon, Kathleen Kelley (Little, Brown, 1995)
Every day, every woman who heads for the office faces the reality of the communication gap. It exists whenever a man's comment makes a woman defensive, and whenever a woman unconsciously casts herself in a subordinate role to a male colleague. Many men haven't learned to define women in terms of their achievement, pigeonholing them instead as wife, daughter, mother, secretary. Women have their own set of myths: it pays to be a good, quiet little worker; so don't make waves. Inadequate communication and fear of challenging the status quo hold women back. Kathleen Reardon's mission is to explain what women - and men - can do about it.